KINERJA KOMISI PEMILIHAN UMUM KOTA SURAKARTA DALAM MENINGKATKAN PARTISIPASI POLITIK PADA PILPRES TAHUN 2014 DI KOTA SURAKARTA - Aris Tri Haryanto, Jemi, Damayanti Suhita & (Transformasi, 2015)
This research uses a qualitative descriptive method. The informants of this research were gathered from the purposive sampling followed by snowball sampling the source of data used in this research is in form of primary and secondary data. The techniques of collecting data are by interview, documentation, and literature study. The data analysis tecnique used in this research is an interactive analysis which consists of data reduction, data presentation, and conclusion.The result of the research of KPU Surakarta’s performance in executing the general election of President and vice President in increasing political participation in 2014 is considered good, in terms of : (1) it is conformed with the applicable laws and regulations; law number 15 of 2011, law number 42 of 2008, law number 14 of 2008, and the regulation of electoral commision that regulates the technical issues. (2) The KPU of Surakarta used strategy and partnership based-approach (office Channeling), like structural approach, Status Classification approach, and cultural approach. (3) The budget for the implementation of the Presidental and vice Presidental election in Surakarta is fully financed by APBN (national budget) in its implementation, it had been effective and efficient, with the presence of DIPA (the checklist of the budget use), from the accountability aspect of the budget use, KPU of Surakarta had been good administration. Moreover, the administration had been reported regulary in accordance with the applicable regulations. (4) The human resources of KPU of Surakarta was very adequate in implementing the 2014 Presidential election as many 11.654 people. (5) The approach used was administrative, consultative, and also supported with the existence of KPU of Surakarta website. (6) the factors that influenced the level of political participation in the Presidental election held in Surakarta were: Personage, Leadership, the effectiveness of the socialization of KPU of Surakarta, The same hope, The quality of the Voters, vision-mission and programs offered by the candidates of President and vice President. (7) The KPU of Surakarta had served all citizens of Surakarta fairly. (8) The research’s result indicate that there is 81,23 % of correlation between the KPU of Surakarta’s performance and the political participation in presidential election of 2014 in Surakarta.Key Words: Performance, KPU of Surakarta, Political Participation.